Predictors of Migraine Subtypes in Young Adults With Ischemic Stroke - Alessandro Pezzini; Mario Grassi; Corrado Lodigiani; Rosalba Patella; Carlo Gandolfo; Federica Casoni; Rossella Musolino; Rocco Salvatore Calabrò; Paolo Bovi; Alessandro Adami; Maria Luisa DeLodovici; Elisabetta Del Zotto; et al. (2010)
the mechanisms underlying the relationship between migraine and ischemic stroke remain uncertain. The aim of the present study was to investigate the predictive value of major cardiovascular risk factors, cardiac interatrial abnormalities, and additional biological markers on migraine subtypes in young adults with ischemic stroke.ischemic stroke patients aged 45 years or younger were consecutively enrolled as part of the Italian Project on Stroke in Young Adults. A comprehensive evaluation was performed including assessment of self-reported migraine and cardiovascular risk factors, interatrial right-to-left shunt, and genotyping to detect factor V Leiden and the G20210A mutation in the prothrombin gene.nine hundred eighty-one patients (mean age, 36.0 ± 7.6 years; 50.7% women) were included. The risk of migraine with aura increased with decreasing number of cardiovascular risk factors (OR, 0.50; 95% CI, 0.24-0.99 for 2 factors or more), increasing number of thrombophilic variants (OR, 2.21; 95% CI, 1.05-4.68 for carriers of at least 1 of the 2), and the presence of right-to-left shunt (OR, 2.41; 95% CI, 1.37-3.45), as compared to patients without migraine. None of these factors had influence on the risk of migraine without aura.in young adults with ischemic stroke, low cardiovascular risk profile, right-to-left shunt, and an underlying procoagulant state are predictors of migraine with aura. The biological effects of these factors should be considered in future studies aimed at investigating the mechanisms linking migraine to brain ischemia.